Coumarin 314 Free Radical Cation: Formation, Properties, and Reactivity Toward Phenolic Antioxidants - Aspee-Lamas, A; Pino-Lopez, E (2012)
We have explored the photogeneration of the coumarin 314 radical cation by using nanosecond laser excitation at wavelengths longer than 400 nm in benzene, acetonitrile, dichloromethane, and aqueous media. In addition, time-resolved absorption spectroscopy measurements allowed detection of the triplet excited state of coumarin 314 (C314) with a maximum absorption at 550 nm in benzene. The triplet excited state has a lifetime of 90 ?s in benzene. It is readily quenched by oxygen (kq = 5.0 × 109 M -1 s-1). From triplet-triplet energy transfer quenching experiments, it is shown that the energy of this triplet excited state is higher than 35 kcal/mol, in accord with the relatively large singlet oxygen quantum yield (?? = 0.25). However, in aqueous media, the coumarin triplet was no longer observed, and instead of that, a long-lived (160 ?s in air-equilibrated solutions) free radical cation with a maximum absorbance at 370 nm was detected. The free radical cation generation, which has a quantum yield of 0.2, occurs by electron photoejection. Moreover, density functional theory (DFT) calculations indicate that at least 40% of the electronic density is placed on the nitrogen atom in aqueous media, which explains its lack of reactivity toward oxygen. On the other hand, rate constant values close to the diffusion rate limit in water (>109 M-1 s-1) were found for the quenching of the C314 free radical cation by phenolic antioxidants. The results have been interpreted by an electron-transfer reaction between the phenolic antioxidant and the radical cation where ion pair formation could be involved. © 2011 American Chemical Society.